2012
DOI: 10.29059/cienciauat.v6i3.51
|View full text |Cite
|
Sign up to set email alerts
|

Listeria sp. y Listeria monocytogenes en pollo congelado: detección por NOM-143-SSA1-1995 y PCR de expendios comerciales de Matamoros y Reynosa, Tamaulipas, México

Abstract: La listeriosis humana había sido hasta hace pocos años una enfermedad poco común. A partir de la década de 1980 empezó a manifestarse como una enfermedad de transmisión alimentaria emergente. La listeriosis humana puede presentarse en casos aislados o en brotes asociados al consumo de alimentos contaminados, como vegetales crudos, leche, quesos frescos y productos cárnicos crudos o insuficientemente cocidos. El objetivo del presente estudio fue determinar la prevalencia de Listeria sp. y L. monocytogenes en mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Some factors, such as variance in geographical environments and differences in the application of antibiotics, can influence the resistance or susceptibility patterns of L. monocytogenes isolates [ 16 ]. Several studies have detected strains of L. monocytogenes (obtained from food sources) that are resistant to one or several antibiotics, even those used for treatment [ 17 , 18 , 19 ]. This complicates its treatment and has generated concern in the health sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some factors, such as variance in geographical environments and differences in the application of antibiotics, can influence the resistance or susceptibility patterns of L. monocytogenes isolates [ 16 ]. Several studies have detected strains of L. monocytogenes (obtained from food sources) that are resistant to one or several antibiotics, even those used for treatment [ 17 , 18 , 19 ]. This complicates its treatment and has generated concern in the health sector.…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, reporting cases of listeriosis is not mandatory, and since there are no epidemiological statistics, the risk it represents to public health is unknown [ 19 , 20 ]. Although the transmission of listeriosis is mainly associated with food, only a few studies have been published on the prevalence or resistance to antibiotics; for example, Cruz-Pulido et al [ 19 ] reported a 1.4% prevalence of L. monocytogenes in frozen chicken from Reynosa, Tamaulipas (which shares a border with the United States). Subsequently, Rubio et al [ 21 ] detected L. monocytogenes in 27.7% of strains isolated from beef samples obtained from cities in the north, center, and south of the country (Monterrey, Mexico City, and Tabasco).…”
Section: Introductionmentioning
confidence: 99%